2014
DOI: 10.1080/00036846.2014.916392
|View full text |Cite
|
Sign up to set email alerts
|

Where they go, what they do and why it matters: the importance of geographic accessibility and social class for decisions relating to higher education institution type, degree level and field of study

Abstract: This article considers the impact of geographic accessibility and social class on school leavers when making decisions relating to higher education institution (HEI) type, degree level and field of study. Using a novel and comprehensive Irish data set, we consider a number of joint decisions facing school leavers in relation to where and what to study and employ a range of bivariate choice models which allows us to control for correlations in these decisions. We find that geographic accessibility and social cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…For example, a number of studies have examined geographic inequalities in higher education accessibility in Ireland and found that potential students who live further away from a higher education institution (HEI) generally fare worse on a range of outcomes. In particular, Cullinan et al (2013a,b) found that travel distance has a significantly negative impact on higher education participation for school leavers from lower social class backgrounds, while Flannery and Cullinan (2014) found that travel distance also impacts on where students choose to study, what they study and at what level they do so. Thus, in this article geographic accessibility to agricultural education in Ireland is considered for the first time and it is argued that close proximity to education will positively affect agricultural innovation.…”
Section: Agricultural Innovation and Spatial Influence Factorsmentioning
confidence: 96%
“…For example, a number of studies have examined geographic inequalities in higher education accessibility in Ireland and found that potential students who live further away from a higher education institution (HEI) generally fare worse on a range of outcomes. In particular, Cullinan et al (2013a,b) found that travel distance has a significantly negative impact on higher education participation for school leavers from lower social class backgrounds, while Flannery and Cullinan (2014) found that travel distance also impacts on where students choose to study, what they study and at what level they do so. Thus, in this article geographic accessibility to agricultural education in Ireland is considered for the first time and it is argued that close proximity to education will positively affect agricultural innovation.…”
Section: Agricultural Innovation and Spatial Influence Factorsmentioning
confidence: 96%
“…For this reason, we use travel distance to the nearest HEI as our measure of geographic accessibility. This networkbased method has been applied in a number of other studies, both in Ireland and internationally (Apparicio, Cloutier, and Shearmur 2007;Witten, Exeter, and Field 2003;Cullinan et al 2013;Flannery and Cullinan 2014;Cullinan, Hynes, and O' Donoghue 2011;Cullinan 2011).…”
Section: Discussionmentioning
confidence: 96%
“…As an extension to this analysis, Flannery and Cullinan (2014) considered the impact of geographic accessibility and social class on decisions relating to the type of HEI, degree level and field of study chosen by school leavers. They found that geographic accessibility and social class play an important role in these choices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They even distinguish between types of institutions. Results indicate that geographical proximity increases the chances of entering education at a university or college (Sa et al 2004;Flannery and Cullinan 2014).…”
Section: Educational Infrastructure and The Transition To Universitymentioning
confidence: 96%